Note on generic singularities of planar flat 3-webs - Agafonov, Sergey I. [UNESP] (Springer Nature, 2017)
We propose a definition of genericity for singular flat planar 3-webs formed by integral curves of implicit ODEs and give a classification of generic singularities of such webs.
Keywords: Primary 53A60; Secondary 34M35